Method for producing coated cathode active material for lithium ion batteries and coated cathode active material
By treating Ni-rich lithium oxide-based electrode materials with water and coating them with boron compounds, the method addresses surface reactions, improving electrochemical performance and cycle stability in lithium-ion batteries.
Patent Information
- Application Number
- JP2024543892
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2022-01-24
- Filing Date
- 2023-01-16
- Publication Date
- 2025-01-30
AI Technical Summary
Existing methods for manufacturing Ni-rich cathode active materials in lithium-ion batteries fail to effectively prevent unwanted reactions on the electrode surface, leading to decomposition of electrolytes and solvents, which adversely affect the electrochemical characteristics and cycle stability.
A method involving the treatment of particle-like lithium oxide-based electrode active materials with water to remove most of the water content, followed by solid-liquid separation, and then coating the materials with boron compounds such as boric acid or its derivatives to form a protective layer, which is further processed through heating to enhance electrochemical performance.
The method results in electrode active materials with improved electrochemical characteristics, reduced resistance in cycling, and enhanced cycle stability, along with decreased gas generation and electrolyte decomposition, as evidenced by TEM analysis.
Smart Images

Figure 2025503144000001 
Figure 2025503144000002 
Figure 2025503144000003
Abstract
Description
[Technical field]
[0001] The present invention relates to a method for producing a method for manufacturing a semiconductor device comprising the steps of: (a) General formula Li 1+x TM 1-x O 2 providing a particulate electrode active material based on a lithiated oxide according to the formula (I), wherein x is in the range of 0 to 0.2 and TM is a combination of metals according to the formula (I): (Ni a Co b Mn c ) 1-d M d (I) (In the formula, a is in the range of 0.6 to 0.99, b is 0 or in the range of 0.01 to 0.2; c is in the range of 0 to 0.2; d is in the range of 0 to 0.1; M is at least one of Al, Mg, Ti, Mo, W, and Zr; a+b+c=1), and (b) treating the particulate electrode active material with water and then removing most of the water by a solid-liquid separation process, thereby obtaining a solid residue; (c) treating the solid residue from step (b) with a boron source and with at least one compound of Mg, Ca, Sr, Ba and Zn selected from their respective sulfates, oxides and hydroxides, thereby obtaining an intermediate; (d) heat treating the intermediate from step (c); The present invention relates to a method for producing a coated electrode active material, comprising: [Background technology]
[0002] Lithium-ion secondary batteries are modern devices for storing energy. Many applications have been considered, from small devices such as mobile phones and laptop computers to car batteries and other e-mobility batteries. Various battery components such as electrolytes, electrode materials and separators have important roles in the performance of the battery. Cathode materials have received particular attention. Several materials have been proposed, such as lithium iron phosphate, lithium cobalt oxide, and lithium nickel cobalt manganese oxide. Extensive research has been conducted, but the solutions found so far still leave room for improvement.
[0003] Currently, particular interest is observed in so-called Ni-rich electrode active materials, for example electrode active materials containing 75 mol % or more of Ni with respect to the total TM content.
[0004] One problem with lithium-ion batteries, especially with Ni-rich electrode active materials, is due to undesirable reactions at the surface of the electrode active material. Such reactions can be the decomposition of the electrolyte or the solvent or both. Therefore, attempts have been made to protect the surface without preventing lithium exchange during charging and discharging. Examples are attempts to coat the electrode active material with, for example, aluminum oxide or calcium oxide (see, for example, US 8,993,051).
[0005] Another theory is that free LiOH or Li 2 CO 3 By washing the electrode active material with water, such free LiOH or Li 2 CO 3 Attempts have been made to remove the above-mentioned cations (see, for example, JP 4,789,066 B, JP 5,139,024 B, and US 2015 / 0372300). However, in some cases, it has been observed that the properties of the resulting electrode active material are not improved. [Prior art documents] [Patent documents]
[0006] [Patent Document 1] US 8,993,051 [Patent Document 2] JP 4,789,066 B [Patent Document 3] JP 5,139,024 B [Patent Document 4] US2015 / 0372300 Summary of the Invention [Problem to be solved by the invention]
[0007] The object of the present invention was to provide a method for producing a Ni-rich electrode active material having good electrochemical properties, and in particular a Ni-rich electrode active material having good electrochemical properties, in particular low resistive growth during cycling. [Means for solving the problem]
[0008] Thus, a method as defined at the outset has been found, hereinafter also called the "method of the invention". The method of the invention comprises the following steps: (a) General formula Li 1+x TM 1-x O 2 providing a particulate electrode active material based on a lithiated oxide according to the formula (I), wherein x is in the range of 0 to 0.2 and TM is a combination of metals according to the formula (I): (Ni a Co b Mn c ) 1-d M d (I) (In the formula, a is in the range of 0.6 to 0.99, b is 0 or in the range of 0.01 to 0.2; c is in the range of 0 to 0.2; d is in the range of 0 to 0.1; M is at least one of Al, Mg, Ti, Mo, W, and Zr; a+b+c=1), and (b) treating the particulate electrode active material with water and then removing most of the water by a solid-liquid separation process, thereby obtaining a solid residue; (c) treating the solid residue from step (b) with a boron source and with at least one compound of Mg, Ca, Sr, Ba and Zn selected from their respective sulfates, oxides and hydroxides, thereby obtaining an intermediate; (d) heat treating the intermediate from step (c); Includes.
[0009] The method of the present invention comprises at least four steps (a), (b), (c) and (d), which in the context of the present invention are also referred to as step (a), step (b), step (c) and step (d), respectively. Steps (a) to (d) are carried out in succession. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0010] In step (a), the method of the invention starts from an electrode active material based on a lithiated oxide of TM, where TM is a combination of metals, TM containing Ni and at least one of Co and Mn, preferably TM containing Co and Al or Co and Mn and optionally Al. Said material is hereinafter also called starting material. Preferably, said electrode active material is a lithiated oxide of TM. Said lithiated oxide of TM may contain less than 1% by weight, preferably less than 0.5% by weight, of impurities originating from its production, such as residual lithium hydroxide, residual lithium carbonate and / or lithium sulfate.
[0011] In one embodiment of the present invention, the particulate electrode active material provided in step (a) has the general formula Li 1+x TM 1-x O 2 wherein TM comprises Ni, at least one transition metal selected from Co and Mn, and optionally at least one element selected from Al and Mg, and x is in the range of 0 to 0.2. Preferably, at least 75 mol % of TM is Ni.
[0012] In one embodiment of the present invention, the starting material has an average particle size (D50) in the range of 3 to 20 μm, preferably 4 to 16 μm. The average particle size can be determined, for example, by light scattering or laser diffraction or electroacoustic spectroscopy. The particles are usually composed of agglomerates from primary particles, and the above particle size refers to the particle size of the secondary particles.
[0013] In one embodiment of the present invention, the starting material is 0.1 to 2.0 m 2 / g. The BET surface area can be determined by nitrogen adsorption after outgassing the sample at 200 °C for 30 minutes and beyond, according to DIN ISO 9277:2010.
[0014] In one embodiment of the present invention, the particulate material provided in step (a) has a moisture content, determined by Karl Fischer titration, in the range of 20 to 2,000 ppm, preferably 50 to 1,200 ppm.
[0015] In one embodiment of the invention, the variable TM corresponds to the general formula (I): (Ni a Co b Mn c ) 1-d M 1 d (I) (wherein a+b+c=1, a is in the range of 0.6 to 0.99, preferably 0.75 to 0.95, and more preferably 0.85 to 0.95; b is 0 or in the range of 0.01 to 0.2, preferably 0.025 to 0.2, and more preferably 0.025 to 0.1; c is in the range of 0 to 0.2, preferably 0.025 to 0.2, and more preferably 0.05 to 0.1; d is in the range of 0 to 0.1, preferably 0 to 0.04; M 1is at least one of Al, Mg, Ti, Nb, Mo, W and Zr, preferably at least one of Al, Ti, Zr and W).
[0016] In one embodiment of the invention, the variable c is zero and M 1 is Al, and d is in the range of 0.01 to 0.05.
[0017] In another embodiment of the invention, the variable TM corresponds to the general formula (Ia): (Ni a* Co b* Al e* ) 1-d* M 2 d* (I a) (In the formula, a * +b * +c * = 1, a * is in the range of 0.75 to 0.95, preferably 0.88 to 0.95, b * is in the range of 0.025 to 0.2, preferably 0.025 to 0.1, e * is in the range of 0.01 to 0.2, more preferably 0.015 to 0.04, d * is in the range of 0 to 0.1, preferably 0 to 0.02, M 2 is at least one of W, Mo, Nb, Mg, Ti or Zr).
[0018] The variable x in formula (Ia) is in the range of 0 to 0.2, preferably 0.01 to 0.1.
[0019] In one embodiment of the present invention, TM corresponds to general formula (I) where x ranges from 0 to 0.2, preferably from 0 to 0.1, and even more preferably from 0.01 to 0.05.
[0020] In one embodiment of the present invention, TM is Ni 0.6 Co 0.2 Mn0.2 , Ni 0.7 Co 0.2 Mn 0.1 , Ni 0.8 Co 0.1 Mn 0.1 , Ni 0.83 Co 0.12 Mn 0.05 , Ni 0.89 Co 0.055 Al 0.055 , Ni 0.91 Co 0.045 Al 0.045 and Ni 0.85 Co 0.1 Mn 0.05 is selected from.
[0021] The electrode active material provided in step (a) usually does not contain conductive carbon, i.e., the content of conductive carbon in the starting material is less than 1 mass %, preferably 0.001 to 1.0 mass %, based on the starting material.
[0022] Some elements are ubiquitous. In the context of the present invention, trace amounts of ubiquitous metals such as sodium, calcium, iron or zinc as impurities are not taken into account in the present specification. Trace amounts in this context mean amounts of 0.02 mol % or less relative to the total metal content of the starting material.
[0023] Trace amounts of sulfate resulting from the synthesis of the particulate electrode active material are also ignored.
[0024] In step (b), the electrode active material provided in step (a) is treated with water. During the course of step (b), the pH value of the water is observed to increase to at least 10, for example 11-13.
[0025] Preferably, the water hardness, in particular calcium, of the aqueous medium used in step (b) is at least partially removed. The use of demineralized water is preferred.
[0026] In one embodiment of the present invention, step (b) is carried out at a temperature in the range of 5 to 85°C, preferably 10 to 60°C.
[0027] In one embodiment of the invention, step (b) is carried out at normal pressure, however, it is preferred to carry out step (b) at elevated pressure, for example at a pressure between 10 mbar and 10 bar above normal pressure, or under suction, for example at a pressure between 50 and 250 mbar below normal pressure, preferably at a pressure between 100 and 200 mbar below normal pressure.
[0028] For example, step (b) can be carried out in a vessel that can be easily drained, e.g., located above a filter device. Such vessels can be filled with the starting material, followed by the introduction of the aqueous medium. In other embodiments, such vessels are filled with the aqueous medium, followed by the introduction of the starting material. In other embodiments, the starting material and the aqueous medium are introduced simultaneously.
[0029] In one embodiment of the present invention, in step (b), the amounts of water and electrode active material have a mass ratio in the range of 1:5 to 5:1, preferably 2:1 to 1:2.
[0030] Step (b) may be supported by a mixing operation, for example by shaking, or in particular by stirring or shearing (see below).
[0031] In one embodiment of the invention, step (b) has a duration in the range of 1 minute to 90 minutes, preferably 1 minute to less than 60 minutes. In embodiments where water treatment and water removal in step (b) are performed overlapping or simultaneously, durations of 5 minutes or more are possible.
[0032] In one embodiment of the invention, the treatment and removal of water according to step (b) are carried out sequentially.
[0033] After or during the treatment with the aqueous medium according to step (b), the water can be removed by any type of filtration, for example by a band filter or a filter press.
[0034] In one embodiment of the present invention, the removal of water is started at least 5 minutes after the start of step (b). Step (c) comprises partially removing water from the treated particulate matter, for example by a method of solid-liquid separation, for example by decantation or preferably by filtration. Said "partial removal" is also called partially separating.
[0035] In one embodiment of step (c), the slurry obtained in step (b) is discharged directly into a centrifuge, such as a decanter centrifuge or a filter centrifuge, or into a filter device, such as a suction filter, or a filter press, or into a belt filter, preferably located directly below the vessel in which step (b) is carried out, after which filtration begins.
[0036] In a particularly preferred embodiment of the present invention, steps (b) and (c) are carried out in a filter press or a stirred filter apparatus, such as a stirred pressure filter or a stirred suction filter (in German, for example "Ruehrfilternutsche"). Removal of the aqueous medium is started by starting the filtration at most 5 minutes, preferably at most 3 minutes, or even immediately after combining the starting material with the aqueous medium according to step (b). On a laboratory scale, steps (b) and (c) can be carried out in a Büchner funnel, and steps (b) and (c) can be supported by manual stirring.
[0037] In a preferred embodiment, step (b) is carried out in a filter apparatus, such as a filter apparatus equipped with an agitator, which allows for agitation of the slurry or filter cake within the filter.
[0038] In one embodiment of the present invention, the removal of water according to step (c) has a duration ranging from 1 minute to 1 hour.
[0039] In one embodiment of the present invention, the stirring in step (b) is carried out at a speed in the range of 1 to 50 revolutions per minute ("rpm"), preferably 5 to 20 rpm, and in another embodiment, 200 to 400 rpm.
[0040] In one embodiment of the present invention, the filter media can be selected from ceramics, sintered glass, sintered metals, organic polymer films, nonwoven fabrics, and woven fabrics.
[0041] In one embodiment of the invention, step (b) comprises the step of: 2 The reaction is carried out in an atmosphere having a carbon dioxide content in the range of, for example, 0.01 to 500 ppm by mass, preferably 0.1 to 50 ppm by mass. 2 The content can be determined by optical methods, for example using infrared light. It is even more preferred to carry out steps (b) and (c) under an atmosphere having a carbon dioxide content below the detection limit of optical methods, for example based on infrared light.
[0042] From step (b), a solid residue is obtained, preferably in the form of a wet filter cake. The moisture content of the solid residue, in particular the filter cake, is in the range of 3-20% by weight, preferably 4-9% by weight.
[0043] In step (c), the solid residue from step (b) is treated with a boron source, such as boric acid or 2 O 3 or LiBO 2 and at least one compound of Mg, Ca, Sr, Ba and Zn, said metals being M 3 Preferred are Sr and Zn, said compounds being selected from their respective sulfates, oxides and hydroxides, whereby intermediates are obtained. Among said compounds of Mg, Ca, Sr, Ba and Zn, preferred are compounds that dissolve in acidic aqueous solutions, for example at pH values in the range of 2 to 5. BaSO 4 and SrSO 4 may be selected, but is not preferred.
[0044] Step (c) may be carried out in the presence of a solvent, for example an alcohol such as ethanol or isopropanol, or water. Preferably, step (c) is carried out in the absence of a solvent.
[0045] In one embodiment of the invention, the compound(s) of Mg, Ca, Sr, Ba and Zn are selected from the group consisting of MgO, Mg(OH) 2 , MgSO 4 , SrO, Sr(OH) 2 , BaO, Ba(OH) 2 , ZnO, ZnSO 4 , and Zn(OH) 2 Preferably, the compound(s) of Mg, Ca, Sr, Ba and Zn is selected from MgO, Mg(OH) 2 , SrO, Sr(OH) 2 , BaO, Ba(OH) 2 , ZnO, ZnSO 4 , and Zn(OH) 2 More preferred are the oxides MgO, CaO, SrO, and ZnO.
[0046] In one embodiment of the present invention, the molar ratio of boron to the compound(s) of Mg, Ca, Sr, Ba and Zn ranges from 10:1 to 1:10, preferably from 6:1 to 1:2.
[0047] In one embodiment of step (c), M 3 The compound(s) above is used in a total amount within the range of 0.1 to 5.0 mol %, preferably 0.2 to 1.0 mol %, based on the TM.
[0048] In one embodiment of step (c), the B source is used in the range of 0.1-3.0 mol % relative to B and TM, preferably 0.2-1.0 mol %.
[0049] The treatment according to step (c) can be carried out in one or more sub-steps, for example with a compound of Mg, Ca, Sr, Ba or Zn in a first sub-step and with a source of boron in a second sub-step, or with a source of boron in a first sub-step and with a compound of Mg, Ca, Sr, Ba or Zn in a second sub-step, but it is preferred to carry out only one treatment step.
[0050] In one embodiment of the present invention, steps (b)-(c) are carried out in the same vessel, for example a filter device with an agitator, for example a pressure filter with an agitator or a suction filter with an agitator. In another embodiment, step (c) is carried out in a blender. Examples of blenders include a plowshare mixer available from Loedige GmbH, a "Wonder Blender" type high shear mixer and grinder available from Osaka Chem.Co.,Ltd. In another embodiment, step (c) is carried out in a blender, for example a lab blender, or a horizontal or vertical mixer capable of applying shear through an additional set of blades.
[0051] In one embodiment of the present invention, step (c) is carried out at a temperature in the range of 5 to 75°C, preferably 10 to 35°C.
[0052] In one embodiment of the invention, step (c) has a duration ranging from 5 minutes to 5 hours. Longer treatment times usually do not provide any advantage.
[0053] Said treating according to step (c) results in a material.
[0054] The method of the present invention further comprises a subsequent step (d): (d) heat treating the material obtained in step (c). Includes.
[0055] The step (d) is 3 Particularly preferred are those embodiments in which said compound(s) of or B is added as an aqueous slurry or solution.
[0056] Step (d) can be carried out in any type of oven, such as a roller hearth kiln, a pusher kiln, a rotary kiln, a pendulum kiln, or, in the case of laboratory scale tests, a muffle oven.
[0057] The temperature of the heat treatment in step (d) may be in the range of 40 to 650° C., preferably 150 to 400° C. The said temperature refers to the maximum temperature in step (d).
[0058] The material resulting from step (d) can be directly subjected to step (d) or the water can be removed by a solid-liquid separation method such as filtration.
[0059] It is preferred to increase the temperature of step (d) stepwise or to increase the temperature gradually or to first dry the material obtained after step (d) at a temperature in the range of 40-250° C. (step (e1)) and then subject it to, for example, above 250-650° C. (step (e2)).
[0060] Said stepwise or gradual temperature increase can be carried out at normal pressure or at reduced pressure, for example from 0.1 ("vacuum") to 500 mbar.
[0061] Step (d) at the maximum temperature may be carried out under normal pressure.
[0062] In one embodiment of the invention, step (d) is carried out under an oxygen-containing atmosphere, such as air, oxygen-enriched air or pure oxygen.
[0063] In embodiments where drying at a temperature in the range of 40 to 250° C. is carried out prior to step (d), such drying may be carried out for a duration of 10 minutes to 20 hours.
[0064] In one embodiment of the invention, step (d) comprises the step of: 2 The reaction is carried out in an atmosphere having a carbon dioxide content in the range of, for example, 0.01 to 500 ppm by mass, preferably 0.1 to 50 ppm by mass. 2 The content can be determined by optical methods, for example using infrared light. It is even more preferred to carry out step (d) under an atmosphere having a carbon dioxide content below the detection limit of optical methods, for example based on infrared light.
[0065] In one embodiment of the present invention, step (d) has a duration ranging from 1 to 10 hours, preferably from 90 minutes to 6 hours.
[0066] In one embodiment of the invention, the lithium content of the electrode active material is reduced by 0.04-1% by weight, preferably by 0.05-0.5%, said reduction mainly affecting the so-called residual lithium, the percentage being relative to the total lithium content of the starting material.
[0067] By carrying out the method of the present invention, an electrode active material having excellent electrochemical properties can be obtained. Without wishing to be bound by any theory, it is believed that the decomposition products of the compound B lead to the removal of the lithium compound deposited on the surface of the electrode active material, and that the decomposition products of the compound M 3 It is believed that this compound leads to the formation of glass.
[0068] Without wishing to be bound by any theory, the method of the invention is 3 It is believed that this cleaning process has less adverse effects on the surface of the electrode active material than a cleaning process that does not include the above compound.
[0069] The cathode active materials obtained by the methods of the present invention have many advantages: Cathodes made from such cathode active materials exhibit improved cycling stability, reduced gassing, and reduced electrolyte decomposition upon cycling, as shown, for example, by transmission electron spectroscopy ("TEM"), resulting in a coating of secondary particles.
[0070] Another aspect of the present invention relates to an electrode active material, hereinafter also referred to as inventive electrode active material or inventive cathode active material, which is obtainable by the inventive process.
[0071] The cathode active material of the present invention is a particulate electrode active material for lithium ion batteries, wherein the material has the general formula Li 1+x TM 1-x O 2and a compound of boron and at least one of Mg, Ca, Sr, Ba and Zn (hereinafter M 3 and TM is a combination of the metals listed above.
[0072] For example, such coatings include 3 , or M 3 B containing sulfates or oxides of 2 O 3 Or it may contain a compound such as Li-B oxide.
[0073] In one embodiment of the invention, the coating has a thickness in the range of 1-15 nm as determined by SEM (scanning electron microscope) or TEM.
[0074] At least partially coated includes embodiments in which all particles of the cathode active material of the present invention are coated, however, in one embodiment, 80-99.9% of all particles of the cathode active material of the present invention are coated, 0.1-20% are uncoated, and preferably 90-99.9% are coated.
[0075] At least partial coating includes an embodiment in which all particles of the cathode active material of the present invention are completely coated. However, in one embodiment, the range of 1-20% of the outer surface of the particles of the cathode active material of the present invention may not be coated. Without wishing to be bound by any theory, it is possible that the coating is enhanced due to certain non-uniformities of the particle surface after step (b), such as hydroxyl content.
[0076] In one embodiment of the present invention, the cathode active material of the present invention has an average particle size (D50) in the range of 3 to 20 μm, preferably 4 to 16 μm. The average particle size can be determined, for example, by light scattering or laser diffraction or electroacoustic spectroscopy. The particles are usually composed of aggregates from primary particles, and the above particle size refers to the particle size of the secondary particles.
[0077] In one embodiment of the present invention, the cathode active material of the present invention has a thickness of 0.1 to 2.0 μm. 2 / g. The BET surface area can be determined by nitrogen adsorption after outgassing the sample at 200 °C for 30 minutes and beyond, according to DIN ISO 9277:2010.
[0078] In one embodiment of the present invention, the cathode active material of the present invention has a water content, as determined by Karl Fischer titration, in the range of 20 to 2,000 ppm, preferably 50 to 1,200 ppm.
[0079] In one embodiment of the present invention, x is in the range of 0 to 0.16, preferably 0 or more and 0.05 or more.
[0080] Formula Li 1+x TM 1-x O 2 in which TM is a metal combination according to general formula (Ia) (Ni a Co b Mn c ) 1-d M d (I a) (In the formula, a is in the range of 0.6 to 0.99, b is 0 or in the range of 0.01 to 0.2; c is in the range of 0 to 0.2; d is in the range of 0 to 0.1; M is at least one of Al, Mg, Ti, Mo, W, and Zr; a+b+c=1) x ranges from 0 to 0.05.
[0081] In another embodiment of the invention, the variable TM corresponds to the general formula (Ia): (Ni a* Co b* Al e* ) 1-d* M2 d* (I a) (In the formula, a * +b * +c * = 1, a * is in the range of 0.75 to 0.95, preferably 0.88 to 0.95, b * is in the range of 0.025 to 0.2, preferably 0.025 to 0.1, e * is in the range of 0.01 to 0.2, more preferably 0.015 to 0.04, d * is in the range of 0 to 0.1, preferably 0 to 0.02, M 2 is at least one of W, Mo, Nb, Mg, Ti or Zr).
[0082] The variable x in formula (Ia) is in the range of 0 to 0.2, preferably 0.01 to 0.1.
[0083] In one embodiment of the present invention, TM corresponds to general formula (I) where x ranges from 0 to 0.2, preferably from 0 to 0.1, and even more preferably from 0.01 to 0.05.
[0084] In one embodiment of the present invention, TM is Ni 0.6 Co 0.2 Mn 0.2 , Ni 0.7 Co 0.2 Mn 0.1 , Ni 0.8 Co 0.1 Mn 0.1 , Ni 0.83 Co 0.12 Mn 0.05 , Ni 0.89 Co 0.055 Al 0.055 , Ni 0.91 Co 0.045 Al 0.045 and Ni 0.85 Co 0.1 Mn 0.05 is selected from.
[0085] The electrode active material of the present invention usually does not contain conductive carbon, that is, the content of conductive carbon in the starting material is less than 1% by mass, preferably 0.001 to 1.0% by mass, based on the starting material.
[0086] Some elements are ubiquitous. In the context of the present invention, trace amounts of ubiquitous metals such as sodium, calcium, iron or zinc as impurities are not taken into account in the present specification. Trace amounts in this context mean amounts of 0.02 mol % or less relative to the total metal content of the starting material.
[0087] In one embodiment of the invention, the cathode active material of the invention has a particle size distribution span in the range of 0.5 to 0.9, the span being defined as [(D90)-(D10)] divided by (D50), all determined by LASER analysis. In another embodiment of the invention, the precursor can have a particle size distribution span in the range of 1.1 to 1.8.
[0088] In one embodiment of the invention, said at least partial coating is present mainly on the outer surface of the secondary particles.
[0089] In one embodiment of the invention, said at least partial coating is glassy or amorphous. Preferably, said coating comprises glassy or amorphous oxides of lithium and boron.
[0090] A further aspect of the present invention relates to electrodes comprising at least one particulate cathode active material according to the present invention. These are particularly useful for lithium-ion batteries. Lithium-ion batteries comprising at least one electrode according to the present invention exhibit good cycling behavior / stability. An electrode comprising at least one particulate cathode active material according to the present invention is also referred to below as the cathode of the present invention or the cathode of the present invention.
[0091] In particular, the cathode of the present invention comprises (A) at least one electrode active material of the present invention; (B) Carbon in a conductive state; (C) a binder material, also called binder (C), and preferably (D) Current collector Contains:
[0092] In a preferred embodiment, the cathode of the present invention comprises, based on the sum of (A), (B) and (C), (A) 80 to 98 mass % of the electrode active material of the present invention, (B) 1 to 17 mass% carbon, (C) 1 to 15 mass % of a binder Contains:
[0093] The cathodes according to the present invention may include additional components. They may include a current collector, such as, but not limited to, aluminum foil. They may further include conductive carbon and a binder.
[0094] The cathode according to the present invention contains a conductively modified carbon, also called carbon (B) for short, which can be selected from soot, activated carbon, carbon nanotubes, graphene, and graphite, and combinations of at least two of the above.
[0095] Suitable binders (C) are preferably selected from organic (co)polymers. Suitable (co)polymers, i.e. homopolymers or copolymers, can be selected, for example, from (co)polymers obtainable by anionic, catalytic or free radical (co)polymerization, in particular from polyethylene, polyacrylonitrile, polybutadiene, polystyrene and copolymers of at least two comonomers selected from ethylene, propylene, styrene, (meth)acrylonitrile and 1,3-butadiene. Polypropylene is also suitable. Polyisoprene and polyacrylates are furthermore suitable. Polyacrylonitrile is particularly preferred.
[0096] In the context of the present invention, polyacrylonitrile is understood to mean not only polyacrylonitrile homopolymers but also copolymers of acrylonitrile with 1,3-butadiene or with styrene. Polyacrylonitrile homopolymers are preferred.
[0097] In the context of the present invention, polyethylene refers not only to homopolyethylenes, but also to polyethylenes containing at least 50 mol % copolymerized ethylene and up to 50 mol % of at least one further comonomer, such as α-olefins, such as propylene, butylene (1-butene), 1-hexene, 1-octene, 1-decene, 1-dodecene, 1-pentene, and also isobutene, vinyl aromatics, such as styrene, and also (meth)acrylic acid, vinyl acetate, vinyl propionate, C 10 copolymers of (meth)acrylic acid. 1 ~C 10 -alkyl esters, in particular methyl acrylate, methyl methacrylate, ethyl acrylate, ethyl methacrylate, n-butyl acrylate, 2-ethylhexyl acrylate, n-butyl methacrylate, 2-ethylhexyl methacrylate, and also copolymers of ethylene with maleic acid, maleic anhydride and itaconic anhydride. The polyethylene may be HDPE or LDPE.
[0098] In the context of the present invention, polypropylene is understood to mean not only homopolypropylene but also copolymers of propylene with at least 50 mol % copolymerized propylene and up to 50 mol % of at least one further comonomer, such as ethylene, and α-olefins, such as butylene, 1-hexene, 1-octene, 1-decene, 1-dodecene and 1-pentene. The polypropylene is preferably isotactic polypropylene or essentially isotactic polypropylene.
[0099] In the context of the present invention, polystyrene refers to homopolymers of styrene as well as acrylonitrile, 1,3-butadiene, (meth)acrylic acid, C 2 styrene, 1,3-butadiene, (meth)acrylic acid, 1 ~C 10-alkyl esters, divinylbenzene, in particular 1,3-divinylbenzene, 1,2-diphenylethylene and α-methylstyrene copolymers are also understood to mean.
[0100] Another preferred binder (C) is polybutadiene.
[0101] Other suitable binders (C) are selected from polyethylene oxide (PEO), cellulose, carboxymethyl cellulose, polyimides and polyvinyl alcohol.
[0102] In one embodiment of the invention, the binder (C) has an average molecular weight M ranging from 50,000 g / mol to 1,000,000 g / mol, preferably up to 500,000 g / mol. W The (co)polymers are selected from those having the formula:
[0103] The binder (C) may be a crosslinked or non-crosslinked (co)polymer.
[0104] In a particularly preferred embodiment of the present invention, the binder (C) is selected from halogenated (co)polymers, in particular fluorinated (co)polymers.Halogenated or fluorinated (co)polymers are understood to mean (co)polymers that contain at least one (co)polymerized (co)monomer with at least one halogen atom or at least one fluorine atom per molecule, more preferably at least two halogen atoms or at least two fluorine atoms per molecule.Examples include polyvinyl chloride, polyvinylidene chloride, polytetrafluoroethylene, polyvinylidene fluoride (PVdF), tetrafluoroethylene-hexafluoropropylene copolymer, vinylidene fluoride-hexafluoropropylene copolymer (PVdF-HFP), vinylidene fluoride-tetrafluoroethylene copolymer, perfluoroalkyl vinyl ether copolymer, ethylene-tetrafluoroethylene copolymer, vinylidene fluoride-chlorotrifluoroethylene copolymer, and ethylene-chlorofluoroethylene copolymer.
[0105] Suitable binders (C) are especially polyvinyl alcohol and halogenated (co)polymers such as polyvinyl chloride or polyvinylidene chloride, especially fluorinated (co)polymers such as polyvinyl fluoride and especially polyvinylidene fluoride and polytetrafluoroethylene.
[0106] The cathode of the present invention may comprise 1 to 15% by weight of binder(s) relative to the cathode active material of the present invention. In another embodiment, the cathode of the present invention may comprise 0.1 to less than 1% by weight of binder(s).
[0107] A further aspect of the invention is a battery containing at least one cathode comprising the cathode active material of the invention, carbon, and a binder, at least one anode, and at least one electrolyte.
[0108] The cathode embodiments of the present invention have already been described in detail above.
[0109] The anode is made of at least one anode active material, such as carbon (graphite), TiO 2 , lithium titanium oxide, silicon or tin. The anode may further comprise a current collector, for example a metal foil such as copper foil.
[0110] The electrolyte may include at least one non-aqueous solvent, at least one electrolyte salt, and optionally, additives.
[0111] The non-aqueous solvent for the electrolyte may be liquid or solid at room temperature and is preferably selected from polymers, cyclic or acyclic ethers, cyclic and acyclic acetals, and cyclic or acyclic organic carbonates.
[0112] Examples of suitable polymers are in particular polyalkylene glycols, preferably poly-C 1 ~C 4 -alkylene glycols, and in particular polyethylene glycols, where the polyethylene glycols are those containing up to 20 mol % of one or more C 1 ~C 4 The polyalkylene glycol may preferably be a polyalkylene glycol having two methyl or ethyl end caps.
[0113] The molecular weight M of suitable polyalkylene glycols, particularly suitable polyethylene glycols, W may be at least 400 g / mol.
[0114] The molecular weight M of suitable polyalkylene glycols, particularly suitable polyethylene glycols, W can be up to 5,000,000 g / mol, preferably up to 2,000,000 g / mol.
[0115] Examples of suitable acyclic ethers are, for example, diisopropyl ether, di-n-butyl ether, 1,2-dimethoxyethane, 1,2-diethoxyethane, with 1,2-dimethoxyethane being preferred.
[0116] Examples of suitable cyclic ethers are tetrahydrofuran and 1,4-dioxane.
[0117] Examples of suitable acyclic acetals are, for example, dimethoxymethane, diethoxymethane, 1,1-dimethoxyethane and 1,1-diethoxyethane.
[0118] An example of a suitable cyclic acetal is 1,3-dioxane, and especially 1,3-dioxolane.
[0119] Examples of suitable acyclic organic carbonates are dimethyl carbonate, ethyl methyl carbonate, and diethyl carbonate.
[0120] Examples of suitable cyclic organic carbonates are compounds according to general formulae (II) and (III) [ka] (In the formula, R 1 , R 2 and R 3 can be the same or different, hydrogen and C 1 ~C 4 -alkyl, for example selected from methyl, ethyl, n-propyl, isopropyl, n-butyl, isobutyl, sec-butyl and tert-butyl, preferably R 2 and R 3 (Both cannot be tert-butyl).
[0121] In a particularly preferred embodiment, R 1 is methyl, R 2 and R 3 are each hydrogen or R 1 , R 2 and R 3 are hydrogen.
[0122] Another preferred cyclic organic carbonate is vinylene carbonate of formula (IV).
[0123] [ka]
[0124] Preferably, the solvent or solvents are used in an aqueous state, ie with a water content in the range of 1 ppm to 0.1% by weight, which can be determined, for example, by Karl Fischer titration.
[0125] The electrolyte (C) further comprises at least one electrolyte salt. Suitable electrolyte salts are in particular lithium salts. Examples of suitable lithium salts include LiPF 6 , LiBF 4 , LiClO 4 , LiAsF 6 , LiCF 3 SO 3 , LiC(C n F 2n+1 SO 2 ) 3 , lithium imide, e.g. LiN(C n F 2n+1 SO 2 ) 2 (wherein n is an integer ranging from 1 to 20), LiN(SO 2 F) 2 , Li 2 SiF 6 , LiSbF 6 , LiAlCl 4 and the general formula (C n F 2n+1 SO 2 ) t It is the salt of YLi. where t=1 when Y is selected from oxygen and sulfur; when Y is selected from nitrogen and phosphorus, t=2; When Y is selected from carbon and silicon, t=3).
[0126] The preferred electrolyte salt is LiC(CF 3 SO 2 ) 3 , LiN(CF 3 SO 2 ) 2 , LiPF 6 , LiBF 4 , LiClO 4 Selected from LiPF 6 and LiN(CF 3 SO 2 ) 2 is particularly preferred.
[0127] In one embodiment of the present invention, the battery according to the present invention comprises one or more separators by which the electrodes are mechanically separated.Suitable separators are polymer films, especially porous polymer films, that are unreactive towards metallic lithium.Particularly suitable materials for the separators are polyolefins, especially film-forming porous polyethylene and film-forming porous polypropylene.
[0128] A separator made of polyolefin, particularly polyethylene or polypropylene, may have a porosity in the range of 35 to 45%. A suitable pore size is, for example, in the range of 30 to 500 nm.
[0129] In another embodiment of the present invention, the separator can be selected from PET nonwoven fabrics filled with inorganic particles. Such separators can have a porosity in the range of 40-55%. Suitable pore sizes are, for example, in the range of 80-750 nm.
[0130] The battery according to the invention may further comprise a housing which may have any shape, for example a cube, or the shape of a cylindrical disk or can. In one variant, a metal foil configured as a pouch is used as the housing.
[0131] The battery according to the invention exhibits good cycling stability and low capacity loss.
[0132] The battery according to the present invention may comprise two or more electrochemical cells that are combined with each other, for example, connected in series or connected in parallel. A series connection is preferred. In the battery according to the present invention, at least one electrochemical cell contains at least one cathode according to the present invention. Preferably, in the electrochemical cell according to the present invention, the majority of the electrochemical cells contain the cathode according to the present invention. Even more preferably, in the battery according to the present invention, all the electrochemical cells contain the cathode according to the present invention.
[0133] The present invention further provides a method for using the battery according to the present invention in equipment, especially mobile equipment.Examples of mobile equipment are vehicles, such as automobiles, bicycles, aircraft, or water vehicles, such as boats or ships.Other examples of mobile equipment are manually operated, such as computers, especially laptops, phones, or powered hand tools, for example in the construction sector, especially drills, battery-powered drivers, or battery-powered staplers.
[0134] The present invention is further illustrated by the following examples. EXAMPLES
[0135] I. Synthesis of Cathode Active Material I.1 Synthesis of precursor TM-OH.1 An aqueous solution of 49 g ammonium sulfate per kg water was placed in a stirred tank reactor. The solution was thermostated at 55° C. and adjusted to a pH value of 12 by adding aqueous sodium hydroxide solution.
[0136] The coprecipitation reaction was started by feeding aqueous transition metal sulfate and aqueous sodium hydroxide solutions simultaneously at a flow ratio of 1.8 with a total flow rate of 8 hours residence time. The transition metal solution contained Ni, Co and Mn in a molar ratio of 8.7:0.5:0.8 and a total transition metal concentration of 1.65 mol / kg. The aqueous sodium hydroxide solution was a 25% by weight sodium hydroxide solution and a 25% by weight ammonia solution in a mass ratio of 6. The pH value was maintained at 12 by feeding the aqueous sodium hydroxide solution separately. Starting from the start of all feeds, the mother liquor was continuously removed. After 33 hours, all feed flows were stopped. The resulting suspension was filtered, washed with distilled water, dried at 120° C. in air and sieved to obtain the mixed transition metal (TM) oxyhydroxide precursor TM-OH.1.
[0137] I.2 Synthesis of basic cathode active material B-CAM.1 Step (a.1): The mixed transition metal oxyhydroxide precursor TM-OH.1 was mixed with LiOH monohydrate in a Li / (Ni+Co+Mn) molar ratio of 1.03. The mixture was heated to 780°C and kept in a mixed gas flow of 100% oxygen for 10 hours. After cooling to room temperature, the resulting powder was deagglomerated and sieved through a 45 μm mesh to obtain the electrode active material B-CAM 1.
[0138] 20 kg of B-CAM.1 was slurried in 10 L of deionized water at room temperature with stirring for 5 minutes. The resulting slurry was transferred to a filter press, pressurized with dry air, and filtered to remove water. The resulting filter cake was dried under dry air at 120° C. for 5 hours to obtain the electrode active material B-CAM 2.
[0139] Using laser diffraction, the D50 was determined to be 14.0 μm using a Malvern Instruments Mastersizer 3000 instrument. The Li and transition metal contents were determined by ICP analysis. The residual moisture content determined at 250 °C was less than 300 ppm.
[0140] II. Synthesis of the Cathode Active Materials of the Present Invention and Comparative Cathode Active Materials II.1 Synthesis of CAM.1 0.40 g of boric acid and 0.07 g of calcium oxide were added to 70 g of B-CAM.2 under homogenization with a mixer, then heat-treated at 300° C. for 2 hours in a forced flow of oxygen, and sieved through a 45 μm mesh to obtain the cathode active material CAM.1 of the present invention.
[0141] II.2 Synthesis of CAM.2 0.46g of boric acid and 0.21g of calcium oxide were added to 80g of B-CAM.2 under homogenization with a mixer, then heat-treated at 300°C for 2 hours in a forced flow of oxygen, and sieved through a 45μm mesh to obtain the cathode active material CAM.2 of the present invention.
[0142] II.3 Synthesis of CAM.3 0.46g of boric acid and 0.42g of calcium oxide were added to 80g of B-CAM.2 under homogenization with a mixer, then heat-treated at 300°C for 2 hours in a forced flow of oxygen, and sieved through a 45μm mesh to obtain the cathode active material CAM.3 of the present invention.
[0143] II.4 Synthesis of CAM.4 0.40g of boric acid and 0.05g of magnesium oxide were added to 70g of B-CAM.2 under homogenization with a mixer, then heat-treated at 300°C for 2 hours in a forced flow of oxygen, and sieved through a 45μm mesh to obtain the cathode active material CAM.4 of the present invention.
[0144] II.5 Synthesis of CAM.5 0.46g of boric acid and 0.15g of magnesium oxide were added to 80g of B-CAM.2 under homogenization with a mixer, then heat-treated at 300°C for 2 hours in a forced flow of oxygen, and sieved through a 45μm mesh to obtain the cathode active material CAM.5 of the present invention.
[0145] II.6 Synthesis of CAM.6 0.46g of boric acid and 0.30g of magnesium oxide were added to 80g of B-CAM.2 under homogenization with a mixer, then heat-treated at 300°C for 2 hours in a forced flow of oxygen, and sieved through a 45μm mesh to obtain the cathode active material CAM.6 of the present invention.
[0146] II.7 Synthesis of CAM.7 0.40g of boric acid and 0.19g of barium oxide were added to 70g of B-CAM.2 under homogenization with a mixer, then heat-treated at 300°C for 2 hours in a forced flow of oxygen, and sieved through a 45μm mesh to obtain the cathode active material CAM.7 of the present invention.
[0147] II.8 Synthesis of CAM.8 0.46g of boric acid and 0.57g of barium oxide were added to 80g of B-CAM.2 under homogenization with a mixer, then heat-treated at 300°C for 2 hours in a forced flow of oxygen, and sieved through a 45μm mesh to obtain the cathode active material CAM.8 of the present invention.
[0148] II.9 Synthesis of CAM.9 0.46g of boric acid and 1.14g of barium oxide were added to 80g of B-CAM.2 under homogenization with a mixer, then heat-treated at 300°C for 2 hours in a forced flow of oxygen, and sieved through a 45μm mesh to obtain the cathode active material CAM.9 of the present invention.
[0149] II.10 Synthesis of CAM.10 0.46g of boric acid and 0.38g of strontium oxide were added to 80g of B-CAM.2 under homogenization with a mixer, then heat-treated at 300°C for 2 hours in a forced flow of oxygen, and sieved through a 45μm mesh to obtain the cathode active material CAM.10 of the present invention.
[0150] II.11 Synthesis of CAM.11 0.46g of boric acid and 0.77g of strontium oxide were added to 80g of B-CAM.2 under homogenization with a mixer, then heat-treated at 300°C for 2 hours in a forced flow of oxygen, and sieved through a 45μm mesh to obtain the cathode active material CAM.11 of the present invention.
[0151] II.12 Synthesis of CAM.12 0.46g of boric acid and 0.30g of zinc oxide were added to 80g of B-CAM.2 under homogenization with a mixer, then heat-treated at 300°C for 2 hours in a forced flow of oxygen, and sieved through a 45μm mesh to obtain the cathode active material CAM.12 of the present invention.
[0152] II.13 Synthesis of CAM.13 0.46g of boric acid and 0.60g of zinc oxide were added to 80g of B-CAM.2 under homogenization with a mixer, then heat-treated at 300°C for 2 hours in a forced flow of oxygen, and sieved through a 45μm mesh to obtain the cathode active material CAM.13 of the present invention.
[0153] II.14 Synthesis of C-CAM.14 0.46 g of boric acid was added to 80 g of B-CAM.2 under homogenization with a mixer, then heat-treated at 300° C. for 2 hours in a forced flow of oxygen, and sieved through a 45 μm mesh to obtain a comparative cathode active material C-CAM.1.
[0154] II.15 Synthesis of C-CAM.15 0.21 g of calcium oxide was added to 80 g of B-CAM.2 under homogenization with a mixer, then heat-treated at 300° C. for 2 hours in a forced flow of oxygen, and sieved through a 45 μm mesh to obtain a comparative cathode active material C-CAM.2.
[0155] II.16 Synthesis of C-CAM.16 0.15 g of magnesium oxide was added to 80 g of B-CAM.2 under homogenization with a mixer, then heat-treated at 300° C. for 2 hours in a forced flow of oxygen, and sieved through a 45 μm mesh to obtain a comparative cathode active material C-CAM.3.
[0156] II.17 Synthesis of C-CAM.17 0.57 g of barium oxide was added to 80 g of B-CAM.2 under homogenization with a mixer, then heat-treated at 300° C. for 2 hours in a forced flow of oxygen, and sieved through a 45 μm mesh to obtain a comparative cathode active material C-CAM.4.
[0157] II.18 Synthesis of C-CAM.18 0.38 g of strontium oxide was added to 80 g of B-CAM.2 under homogenization with a mixer, then heat-treated at 300° C. for 2 hours in a forced flow of oxygen, and sieved through a 45 μm mesh to obtain a comparative cathode active material C-CAM.5.
[0158] II.19 Synthesis of C-CAM.19 0.30 g of zinc oxide was added to 80 g of B-CAM.2 under homogenization with a mixer, then heat-treated at 300° C. for 2 hours in a forced flow of oxygen, and sieved through a 45 μm mesh to obtain a comparative cathode active material C-CAM.6.
[0159] III. Testing of Cathode Active Materials III.1 Electrode fabrication III.1.1 Positive electrode production PVDF binder (Solef® 5130) was dissolved in NMP (Merck) to make a 7.5 wt% solution. For electrode preparation, the binder solution (3 wt%), graphite (SFG6L, 2 wt%) and carbon black (Super C65, 1 wt%) were suspended in NMP. After mixing using a planetary centrifugal mixer (ARE-250, Thinky Corp.; Japan), either the cathode active material CAM.1-CAM.13 of the present invention or the comparative cathode active material (94 wt%) was added and the suspension was mixed again to obtain a lump-free slurry. The solids content of the slurry was adjusted to 65%. The slurry was applied onto Al foil using a KTF-S roll-to-roll coater (Mathis AG). All electrodes were calendered before use. The thickness of the cathode material was 70 μm with a density of 15 mg / cm. 2 All electrodes were dried at 105 °C for 7 h before cell assembly.
[0160] III.2 Preparation of electrolyte 12.7% by weight of LiPF based on the total weight of EL base 1 6 A base electrolyte composition (EL Base 1) was prepared containing 26.2 wt. % ethylene carbonate (EC), and 61.1 wt. % ethyl methyl carbonate (EMC).
[0161] III.3 Test cell fabrication: coin-type half cell A coin-shaped half-cell (20 mm in diameter, 3.2 mm in thickness) containing the cathode prepared in III.1.1 and lithium metal foil as the working electrode and counter electrode was assembled by injecting 0.15 mL of the electrolyte prepared in III.2, and sealed in an Ar-filled glove box. The cathode, separator, and lithium metal foil were stacked together to prepare a coin-shaped half-cell.
[0162] IV Cell performance evaluation IV.1 Performance evaluation of coin-type half-cell The battery performance was evaluated using the coin-type cell described in III.3.1. The initial capacity and coulombic efficiency were measured as the initial performance, and the cycle capacity retention and resistance growth at 25°C and 45°C were measured as the long-term stability of the cell.
[0163] IV.1.1 Cycling performance at 25°C Cycling performance at 25° C. was measured as follows: The cells were tested at 25°C in the voltage range of 4.3 V to 3.0 V, and charging was performed in CC-CV mode, i.e., a constant current (CC) of 0.5 C was applied until 4.3 V was reached, and then held at 4.3 V (CV) until 0.01 C was reached. After a rest period of 10 min, discharging was performed in CC mode from 1 C to 3.0 V. The capacity retention was calculated by the ratio of the discharge capacity of the first cycle to that of the 100th cycle.
[0164] IV.1.2 Cycling performance at 45°C Cycling performance at 45°C was measured as follows: The cells were cycled at 45 °C in the voltage range of 4.25 V to 3.0 V, charging was performed in CC-CV mode, i.e., a constant current of 0.5 C (CC) was applied until 4.25 V was reached and held at 4.25 V (CV) until 0.01 C was reached. After a rest period of 10 min, discharge was performed in CC mode from 0.5 C to 3.0 V. The capacity retention was calculated by the ratio of the discharge capacity of the first cycle and the 100th cycle. In parallel, the increase in cell resistance during cycling was monitored from the initial drop in cell voltage during discharge.
[0165] [Table 1]
[0166] [Table 2]
Claims
1. The following steps: (a) General formula Li 1+x T.M. 1-x O 2 wherein x is in the range of 0 to 0.2 and T M is a combination of metals according to general formula (I). (Ni a Co b Mr c ) 1-d M d (I) (wherein a is in the range of 0.6 to 0.99; b is 0 or in the range of 0.01 to 0.2; c is in the range of 0 to 0.2; d is in the range of 0 to 0.1; M is at least one of Al, Mg, Ti, Mo, W, and Zr; a+b+c=1; (b) treating the particulate electrode active material with water and then removing most of the water by a solid-liquid separation process, thereby obtaining a solid residue; (c) treating the solid residue from step (b) with a boron source and with at least one compound of Mg, Ca, Sr, Ba and Zn selected from their respective sulfates, oxides and hydroxides, thereby obtaining an intermediate; (d) heat treating the intermediate from step (c); A method of making a coated cathode active material comprising:
2. 2. The method of claim 1, wherein x ranges from 0 to 0.
05.
3. 3. The process of claim 1 or 2, wherein step (c) is carried out in the absence of a solvent.
4. The compound(s) of Mg, Ca, Sr, Ba and Zn is / are: MgO, Mg(OH) 2 , SrO, Sr(OH) 2 , BaO, Ba(OH) 2 , ZnO, ZnSO 4 , and Zn(OH) 2 The method according to claim 1 or 2, wherein the
5. 3. The method of claim 1 or 2, wherein the boron source is boric acid.
6. 3. The method according to claim 1 or 2, wherein the molar ratio of boron to the compound(s) of Mg, Ca, Sr, Ba and Zn is in the range of 10:1 to 1:
10.
7. A particulate electrode active material for a lithium ion battery, the material having the general formula Li 1+x T.M. 1-x O 2 and an at least partial coating based on a compound of boron and at least one compound of Mg, Ca, Sr, Ba and Zn, where x is in the range of 0 to 0.2, and the formula Li 1+x T.M. 1-x O 2 where TM is a combination of metals according to general formula (I) (Ni a Co b Mr c ) 1-d M d (I) (wherein a is in the range of 0.6 to 0.99; b is 0 or in the range of 0.01 to 0.2; c is in the range of 0 to 0.2; d is in the range of 0 to 0.1; M is at least one of Al, Mg, Ti, Mo, W, and Zr; a+b+c=1), a particulate electrode active material.
8. The particulate electrode active material according to claim 7, wherein x is in the range of 0 to 0.
05.
9. 9. A particulate electrode active material according to claim 7 or 8, wherein the at least partial coating is present primarily on the outer surfaces of the secondary particles.
10. 9. A particulate electrode active material according to claim 7 or 8, wherein the at least partial coating is glassy or amorphous.
11. 9. A particulate electrode active material according to claim 7 or 8, wherein the coating comprises glassy or amorphous oxides of lithium and boron.
12. (A) at least one particulate material according to claim 7 or 8; (B) carbon in a conductive state; and (C) Binder polymer a cathode.
13. 13. An electrochemical cell comprising at least one cathode according to claim 12.
Citation Information
Patent Citations
Process for making a cathode active material for lithium ion batteries, and cathode active material
EP3902037A1
Cathode active material for lithium secondary battery and lithium secondary battery using the same
KR1020110063335A
JP4,789,066B
JP5,139,024B
Nickel composite hydroxide particle and process for producing the same, positive electrode active material for non-aqueous electrolyte secondary battery and process for producing the same, and non-aqueous electrolyte secondary battery
US20150372300A1